MODERATE EFFECT ON THE INFLUENCE OF ATTITUDE AND STOCK MARKET INVESTORS IN DKI JAKARTA - Anika Yuniarti; Farah Margaretha Leon (OPTIMA, 2022)
Psychological factors have an influence on decisions in stock investment. Such as cognitive abilities and financial considerations that can influence investors' decisions. This explains that a person's attitude has a direct impact on an individual's behavioral intentions in making decisions. Therefore, this study aims to investigate the direct impact of investor attitudes on behavioral intentions in the stock market and investigate the moderating effect of cognitive relationships and financial considerations on investors' attitudes and behavioral intentions in the stock market. A total of 150 samples used in this study refer to investors in DKI Jakarta who have invested in stocks/bonds/mutual funds within the last 5 years. Method Analysis of the data using the Structural Equation Modeling (SEM) analysis tool. The findings of this study are investors' attitudes have a positive and significant effect on the behavioral intentions of the stock market. Therefore, this study can be used as a reference material for policy makers, stock market regulators, and financial service providers to pay more attention to the influence of stock market attitudes and behavioral intentions.